Utility of Global Hemostatic Assays in Patients with Bleeding Disorders of Unknown Cause - Mehic, Dino; Assinger, Alice; Gebhart, Johanna (Hämostaseologie, 2024)
Bleeding disorder of unknown cause (BDUC) is a diagnosis of exclusion after exhaustive evaluation of plasmatic coagulation and platelet function. This review explores the utility of global hemostatic assays as confirmatory tests and in elucidating the pathophysiology of BDUC. Unlike traditional hemostatic tests that focus on coagulation factors, global assays are conducted both in plasma and also whole blood. These assays provide a more comprehensive understanding of the cell-based model of coagulation, aid in the identification of plasmatic factor abnormalities that may reduce hemostatic capacity, and allow for the assessment of impaired platelet–endothelial interactions under shear stress, as well as hyperfibrinolytic states. While clinical tests such as skin bleeding time and global assays such as PFA-100 exhibit limited diagnostic capacity, the role of viscoelastic testing in identifying hemostatic dysfunction in patients with BDUC remains unclear. Thrombin generation assays have shown variable results in BDUC patients; some studies demonstrate differences compared with healthy controls or reference values, whereas others question its clinical utility. Fibrinolysis assessment in vitro remains challenging, with studies employing euglobulin clot lysis time, plasma clot lysis time, and fluorogenic plasmin generation yielding inconclusive or conflicting results. Notably, recent studies suggest that microfluidic analysis unveils shear-dependent platelet function defects in BDUC patients, undetected by conventional platelet function assays. Overall, global assays might be helpful for exploring underlying hemostatic impairments, when conventional hemostatic laboratory tests yield no results. However, due to limited data and/or discrepant results, further research is needed to evaluate the utility of global assays as screening tools.
Keywords: global assays; von Willebrand disease; platelet function defects; hemophilia A/B; BDUC